Upaya Peningkatan Literasi, Numerasi dan Teknologi Mengajar Melalui Program Kampus Mengajar di SD Negeri 20 Tana-Tana Kabupaten Takalar - Ramlah Muh. Idris. T; Erwin Nurdiansyah; Sri Hastati; Ince Prabu Setiawan; Nasaruddin Nasaruddin (STKIP Andi Matappa Pangkep, 2022)
Kampus Mengajar Batch 1 is part of the Merdeka Campus Program which involves all students in Indonesia to assist the teaching and learning process in schools, especially at the Elementary School level which has C Accreditation and has the 3T predicate and provides opportunities for students to learn and develop themselves. One of the target schools in this program is SD Negeri 20 Tana-Tana which is located in Takalar Regency. Kampus Mengajar program as part of the MBKM program has activities in the form of teaching activities (literacy and numeracy), technology adaptation, and school administration assistance. With the aim of providing solutions for schools affected by the pandemic by empowering students who live in areas around the school to assist in providing optimal educational services to all students in limited and critical conditions during the pandemic as well as assisting in the implementation of learning that focuses on efforts to increase literacy and numeration. The implementation method in the Teaching Campus program has 4 stages: Situation Analysis; Preparation; Implementation; Result Evaluation. This program has a positive impact on students such as increasing motivation and interest in learning, improving literacy and numeracy skills and the effectiveness of the learning process.